The right to education or freedom of education: constitutional and sectoral aspects The right to education or freedom of education: constitutional and sectoral aspects - Микола Снігур; Лаура Бзова (Конституційно-правові академічні студії, 2024)
This article analyses the distinction between the right to education and freedom of education in the decisions of the Constitutional Court of Ukraine and the European Court of Human Rights.  The article deals with the issues of legislative regulation of the right to education. The author analyses international and national legal acts on the right to education, problems of reforming education and science in the context of the Association of Ukraine and the European Union. The author considers optimisation of the organisation and conduct of scientific research and general approaches to education reform aimed at innovative development of education.